Raceways, rebates, and retrofits: an exploration of several American cities’ policies to facilitate electric vehicle purchase and usage - James Wood; Ankur Jain (International Journal of Urban Sustainable Development, 2021)
Plug-in Electric Vehicles (PEVs) form a critical part of the infrastructure needed for sustainable transportation. Local governments are expected to play a key role in ensuring widespread adoption of PEVs by their residents. This study specifically investigates how large American cities have used the policy process to prepare for broader PEV usage. Based on a questionnaire sent to policy leaders in major American cities, this study investigates issues of building codes, city-utility relations, tax incentives for PEV users, and social equity. The study identifies and analyzes common and influential policies perceived as being most effective at advancing PEV adoption. Findings suggest that cities are either not preparing for PEVs at all, or are preparing in a very substantive and tech-savvy manner. Policymakers also highlight key areas of needed focus, and lay out ways in which regulators and electricity providers can aid in PEV adoption.